2009
DOI: 10.1143/jpsj.78.074714
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Phase Diagram of the Non-centrosymmetric Antiferromagnet CeCoGe3

Abstract: We present a detailed study of the high pressure phase diagram of the non-centrosymmetric antiferromagnet CeCoGe 3 by measurements of the ac calorimetry in a diamond anvil pressure cell. Under high pressure the magnetic ordering temperature shows a step like decrease due to various successive magnetic phases under high pressure. The magnetic order disappears at a critical pressure of p c % 5:5 GPa. Around the critical pressure bulk superconductivity has been detected in the ac calorimetric measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
(23 reference statements)
0
28
0
Order By: Relevance
“…16). The heat capacity jump (∆C) at the superconducting transition [72], CeIrSi 3 [75], CeCoGe 3 [77] and CeIrGe 3 [42]. T * in panel (a) denotes an anomaly observed in the resistivity and magneticsusceptibility measurements [39].…”
Section: Temperature-pressure Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…16). The heat capacity jump (∆C) at the superconducting transition [72], CeIrSi 3 [75], CeCoGe 3 [77] and CeIrGe 3 [42]. T * in panel (a) denotes an anomaly observed in the resistivity and magneticsusceptibility measurements [39].…”
Section: Temperature-pressure Phase Diagrammentioning
confidence: 99%
“…a at 2.85 GPa b at 2.6 GPa c at 2.65 GPa d determined from heat-capacity measurements [77]. e determined from electrical-resistivity measurements [43].…”
Section: Quantum Criticality and Non-fermi Liquidmentioning
confidence: 99%
“…The irreducible representation point group for the tetragonal structure of CePt 3 Si is C 4v , in which Rashba-type ASOC exists, which provides the key to understanding the intriguing superconducting behavior of CePt 3 Si [7][8][9]. Following CePt 3 Si many NCSs have been identified that present interesting superconducting properties, including Li 2 (Pd,Pt) 3 B [10,11], CeRhSi 3 [12,13], CeIrSi 3 [14], CeCoGe 3 [15,16], CeIrGe 3 [17], LaNiC 2 [18][19][20], BaPtSi 3 [21], (Rh,Ir)Ga 9 [22,23], Mg 10 Ir 19 B 16 [24], Mo 3 Al 2 C [25], LaRhSi 3 [26], Ca(Ir,Pt)Si 3 [27], Re 3 W [28], Nb 0.18 Re 0.12 [29], Re 6 Zr [30], La(Pd,Pt)Si 3 [31], Ca 3 Ir 4 Ge 4 [32], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, like CePt 3 Si, a Rashba-type ASOC is present in these CeMX 3 compounds too, leading to an exotic superconducting ground state in them [12][13][14][15][16][17][33][34][35]. Like CePt 3 Si, they also exhibit heavy-fermion behavior and undergo a long-range antiferromagnetic ordering; however, they become superconducting only under the application of pressure [12][13][14][15][16][17][33][34][35]. The above-mentioned Ce-based NCSs are situated close to a magnetic quantum critical point, making it difficult to explore the effects of ASOC and inversion symmetry breaking on superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The high pressure phase diagram of CeCoGe 3 is quite complicated demonstrating six different phases. 13) Magnetic order vanishes around 55 kbar, and superconductivity is observed in the range of 54-75 kbar.…”
mentioning
confidence: 99%